2001
DOI: 10.1002/pola.1218
|View full text |Cite
|
Sign up to set email alerts
|

Novel synthesis of polyimide–polyhybridsiloxane block copolymers via polyhydrosilylation: Characterization and physical properties

Abstract: The insertion of soft polysiloxane segments into a polyimide backbone introduces changes in its properties (processability, low surface tension, gas permeability, and lower dielectric constant). Generally, these polyimide–polysiloxane copolymers are synthesized by the condensation of a dianhydride with an aromatic diamine and an amine telechelic polysiloxane, or by transimidization between an aminopyridine‐terminated oligoimide and an amine end‐capped oligosiloxane. This study investigated another route to obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…They used allyl group telechelic PI moiety and various size of hydrosilane telechelic polyhybridsiloxane, through hydrosilylation reaction, to prepare a series of PIS alternating block copolymers containing 36, 54 and 75 wt % of PI. 18 The resulting PIS copolymers exhibited good performances in terms of both thermomechanical and chemical properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They used allyl group telechelic PI moiety and various size of hydrosilane telechelic polyhybridsiloxane, through hydrosilylation reaction, to prepare a series of PIS alternating block copolymers containing 36, 54 and 75 wt % of PI. 18 The resulting PIS copolymers exhibited good performances in terms of both thermomechanical and chemical properties.…”
mentioning
confidence: 99%
“…Andre et al [18][19][20][21][22] reported a series of studies about fluorinated TPE. They used allyl group telechelic PI moiety and various size of hydrosilane telechelic polyhybridsiloxane, through hydrosilylation reaction, to prepare a series of PIS alternating block copolymers containing 36, 54 and 75 wt % of PI.…”
mentioning
confidence: 99%
“…[7][8][9][10][11] However, rubber properties had not been emphasized in these reports. Andre et al [7][8][9][10] reported a series of studies about fluorinated polysiloxane type TPE. They used allyl group telechelic PI moiety and various sized hydrosilane telechelic polyhybridsiloxane, through hydrosilylation reaction, to prepare a series of PI/polysiloxane alternating block copolymer TPE.…”
mentioning
confidence: 91%
“…However, the numbers of polysiloxane type TPEs discovered and studied has been limited. [6][7][8][9][10][11] Kajiyama et al 6 reported the synthesis of copolymers based on poly(dimethylsiloxane) (PDMS) and N-phenylated polyureas (the hard segment). In their study, the oligomer of ,!-bis(3-aminopropyl) polydimethylsiloxane (APPS, number-average molecular weight M n ¼ 1720 and 2740 gÁmol À1 ) and , 0 -dianilino-p-xylene (DAX) were used to react with 4,4 0 -methylenebis (phenyl isocyanate) (MBI) by the addition solution polymerization to synthesize multiblock copolymers.…”
mentioning
confidence: 99%
See 1 more Smart Citation